Ingen kan gå fri av mørket - Fossum-Kielland, Victoria (Peripeti, 2012)
This article emphasizes the aesthetic and ethical dimensions of fictional violence in two contemporary Scandinavian theatre productions. I discuss and compare the performances Villa Salò by the Danish group SIGNA and The Wild Duck, Part 2 Director’s Cut by the Norwegian performing arts duo Vegard Vinge and Ida Müller, with an emphasis on their use of violence as an aesthetic strategy.